2022
DOI: 10.1002/imhj.21971
|View full text |Cite
|
Sign up to set email alerts
|

Validation of parental stress scale in a Greek sample of mothers with infants from 0 to 12 months

Abstract: Parenting an offspring is a rewarding, albeit challenging task, often accompanied by high levels of stress. It is important to accurately assess the stress associated with parenting, as severe forms of stress may affect the parent‐child dyad and lead to poor child outcomes. The aim of this study was to translate and validate the Parental Stress Scale (PSS) in the Greek population. We implemented forward and back translation and conducted a pilot test. A total of 735 mothers (Mage = 34.6) with infants aged 0–12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 62 publications
1
0
0
Order By: Relevance
“…This phenomenon has also been observed in the study by Leung et al [ 40 ] which suggested that the PSS may pose difficulties for parents with low levels of stress. In terms of internal consistency, the indices were optimal and in line with those that were described in the literature [ 30 , 31 , 32 ], with slightly higher values being identified than those that were obtained in other validation studies of the instrument [ 18 , 34 , 36 , 41 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 82%
“…This phenomenon has also been observed in the study by Leung et al [ 40 ] which suggested that the PSS may pose difficulties for parents with low levels of stress. In terms of internal consistency, the indices were optimal and in line with those that were described in the literature [ 30 , 31 , 32 ], with slightly higher values being identified than those that were obtained in other validation studies of the instrument [ 18 , 34 , 36 , 41 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, there are studies [27,34,35] in the literature that have altered the scale (e.g., score in a 4-point Likert scale instead of the original 5-point, drop-out items, used in grandparents). Recently, a Greek validation study [28], in mothers of healthy infants 0-12 months old, revealed two underlying factors (positive and negative aspects of parenting), confirming the validity of the scale.…”
Section: Literature Reviewmentioning
confidence: 79%
“…Specifically, Zelman et al [29] replicated the original four-factor structure in children with newly diagnosed asthma, diabetes, epilepsy, food allergy and juvenile arthritis, concluding that the PSS is a valid and reliable tool for these parents. Some studies in the literature [26][27][28] identified a two-factor solution as the best model fit; however, Pontoppidan et al [26] suggested that the four factors may represent subdivisions of two factors, called parental stressors and parental satisfaction. The same hypothesis was stated in the original study, where Berry and Jones [2] supported the dichotomy (positive and negative) of the parenting experiences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations